2020
DOI: 10.18203/2349-3933.ijam20205480
|View full text |Cite
|
Sign up to set email alerts
|

Determining COVID-19 disease severity and outcome using sequential chest radiograph in a new designated COVID-19 hospital

Abstract: Background: COVID-19 pandemic to date has recorded around 37 million cases across the world. This study was done to appraise the prognostic importance of portable chest X-ray (CXR) and the Brixia scoring was then used to predict the outcome variables like hypoxia, non-invasive ventilation, intubation, sepsis, multiple organ dysfunction syndrome (MODS), recovery, death and post corona sequalae.Methods: A 100 reverse transcriptase-polymerase chain reaction (RT-PCR) confirmed COVID-19 infection were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Our study shows a significant difference between the patient's Brixia Score with D-Dimer <2 µg/mL and D Dimer ≥2 µg/mL with a p<0.001 (p<0.05) which means there is a relationship between Brixia Score and D-Dimer. This is in line with other studies that there is a significant relationship between Brixia Score with D-Dimer levels in patients, where a higher D-Dimer level is accompanied by a higher Brixia Score (Munirathnam et al, 2020;Viradanti and Kusmala, 2021;Garg et al, 2022). Some previous research reports that most COVID-19 patients have elevated D-Dimer levels due to excessive inflammatory response of lung parenchymal cells and edothelial cells in the lung blood vessels that causes dysregulation in the coagulation system.…”
Section: Sample Characteristicssupporting
confidence: 91%
“…Our study shows a significant difference between the patient's Brixia Score with D-Dimer <2 µg/mL and D Dimer ≥2 µg/mL with a p<0.001 (p<0.05) which means there is a relationship between Brixia Score and D-Dimer. This is in line with other studies that there is a significant relationship between Brixia Score with D-Dimer levels in patients, where a higher D-Dimer level is accompanied by a higher Brixia Score (Munirathnam et al, 2020;Viradanti and Kusmala, 2021;Garg et al, 2022). Some previous research reports that most COVID-19 patients have elevated D-Dimer levels due to excessive inflammatory response of lung parenchymal cells and edothelial cells in the lung blood vessels that causes dysregulation in the coagulation system.…”
Section: Sample Characteristicssupporting
confidence: 91%
“…Our study confirms the main radiological characteristics of COVID-19 described in previous studies. BRIXIA score was significantly higher in patients with severe clinical disease presentation (59,8% high-very high mortality score), which has also been showcased in similar studies [9][10][11][12]. In addition, a lower RALE score was associated with better oxygenation as reflected by higher PaO2/FiO2.…”
Section: Discussionsupporting
confidence: 72%
“…The study results conducted by Setiawati et al, 18 Maroldi et al, 19 and Munirathnam et al 20 showed that the Brixia score correlated significantly with the severity of COVID-19 patients clinically. Maroldi et al 19 and Munirathnam et al 20 also found that Brixia scores were external predictors of hospitalized COVID-19 patients, whether surviving or dying.…”
Section: Discussionmentioning
confidence: 93%